Konsep Maqamat dan Ahwal Sufi: Suatu Penilaian - Wan Abdullah, Wan Suhaimi (Jurnal Usuluddin, 1999)
The concept of maqamat and ahwal is one of the most important sufism doctrine in Islam which played an efficient roles in the sufi’s spiritual journey. It is still remain as an effective steps for the sufis to reach their spiritual destination. But is this, the spiritual need, is the only aspect that the concept worked, or there is a posibility, with such interpretation, to make it an effective method for non-spiritual journey or human development’ This article is an attemption to answer this question and tries to propose some point of view about it.